2008
DOI: 10.1109/tit.2008.924685
|View full text |Cite
|
Sign up to set email alerts
|

On the Mutual Information Distribution of OFDM-Based Spatial Multiplexing: Exact Variance and Outage Approximation

Abstract: Index Terms-multiple-input-multiple-output (MIMO) systems, mutual information, orthogonal frequency-division multiplexing (OFDM).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 37 publications
(114 reference statements)
0
56
0
Order By: Relevance
“…In a cellular network with Rayleigh flat fading, since the achievable rate is modeled by a normally distributed random variable [30], [31], with Lemma 1, Lemma 2 and Corollary 1, we have the following theorem for PFS. Proof: Please refer to Appendix D. We now have the important theoretical result for PFC.…”
Section: B Theoretical Results For Pfs and Pfcmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cellular network with Rayleigh flat fading, since the achievable rate is modeled by a normally distributed random variable [30], [31], with Lemma 1, Lemma 2 and Corollary 1, we have the following theorem for PFS. Proof: Please refer to Appendix D. We now have the important theoretical result for PFC.…”
Section: B Theoretical Results For Pfs and Pfcmentioning
confidence: 99%
“…Smith and McKay etc. [30], [31] have shown that, in Rayleigh or Ricean fading networks, the achievable rate R = log 2 [1 + SNR] can be approximated modeled by a normally distributed random variable with extremely high accuracy. Specially, for a single-input-singleoutput (SISO) link over a Rayleigh flat fading channel, the Normal distribution is characterized by a mean and variance given as follows Specifically, with (19), (20) and (21), we obtain the Normal distribution that characterizes R…”
Section: Analysis Of Pfc Over a Rayleigh Flat Fading Channelmentioning
confidence: 99%
“…Note that the received signal power has been increased by T N times in formula (14) and thus, the channel capacity is given as 2 2 2 log 1 log 1 In figure 3, result are drawn with vary number of transmit and receive for example NT=NR=1 for SISO system, NT=1 and NR=2 for SIMO system and NT=NR=4 is a MIMO system. It is clear from the figure, that the SIMO and MISO channel has nearly same performance.…”
Section: Csi Is Availed At the Transmitter Sidementioning
confidence: 99%
“…In the sequel, we consider the capacity of the MIMO channel when the channel gains between transmit and received antennas are correlated [6][7][8][9][10]. When the SNR is high, the deterministic channel capacity can be approximated as constrained to be a unity [11][12][13][14][15][16]. From (5), then, the MIMO channel is given as log det log det( ) log det( )…”
Section: Mimo Channel Capacity In the Presence Of Antenna Correlamentioning
confidence: 99%
“…[28] and [29] have shown that, in Rayleigh or Ricean fading networks, the Shannon capacity R = log 2 [1+SNR] can be accurately approximated by Normal distribution. Specially, for a SISO link over a Rayleigh flat fading channel where SNR is exponential distributed, the Normal distribution is characterized by a mean and variance given as follows…”
Section: Analysis Of Pfsc Over a Rayleigh Flat Fading Channelmentioning
confidence: 99%